2017
DOI: 10.4172/0974-8369.1000382
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Mature Cystic Teratoma and Endometrioma in an Ovarian Cyst

Abstract: We report a rare case of association between a mature cystic teratoma (MCT) and an endometrioma in the ovary. This entity is extremely rare and its diagnostic is a challenge clinically and radiologically. To our knowledge we report the fourth case of the coexistence of a non-neoplastic endometrioma and a benign neoplastic mature cystic teratoma in the left ovary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Some studies reported conflicting results [9], but the results that MCTs occur more on the right side are dominant [10,11,12]. In addition, they can be located at the midline and in paraxial regions of the body and unusual locations, including lungs or ilea [13]. In approximately 10-15% of cases, they are on both sides [14].…”
Section: Epidemiology and Clinical Findingsmentioning
confidence: 99%
“…Some studies reported conflicting results [9], but the results that MCTs occur more on the right side are dominant [10,11,12]. In addition, they can be located at the midline and in paraxial regions of the body and unusual locations, including lungs or ilea [13]. In approximately 10-15% of cases, they are on both sides [14].…”
Section: Epidemiology and Clinical Findingsmentioning
confidence: 99%